2019
DOI: 10.1002/jmor.21086
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of microglia/macrophages and granulocytes into the Mauthner axon myelin sheath following spinal cord injury of the adult goldfish, Carassius auratus

Abstract: Rapid activation of resident glia occurs after spinal cord injury. Somewhat later, innate and adaptive immune responses occur with the invasion of peripheral immune cells into the wound site. The activation of resident and peripheral immune cells has been postulated to play harmful as well as beneficial roles in the regenerative process. Mauthner cells, large identifiable neurons located in the hindbrain of most fish and amphibians, provided the opportunity to study the morphological relationship between react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Acute spinal cord trauma damages the vasculature, leading to rupture of the blood–brain barrier, induces acute mechanical compression of the myelin sheath, generates myelin debris, and triggers a cascade of pathological processes, including immune cell infiltration and activation ( Kopper and Gensel, 2018 ; Koganti et al, 2020 ). The sustained presence of myelin debris at the injury site of the spinal cord leads to neurological functional recovery failure because the accumulation of myelin debris containing inhibitor molecules resists axon regeneration ( Cunha et al, 2020 ; Liu Y. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute spinal cord trauma damages the vasculature, leading to rupture of the blood–brain barrier, induces acute mechanical compression of the myelin sheath, generates myelin debris, and triggers a cascade of pathological processes, including immune cell infiltration and activation ( Kopper and Gensel, 2018 ; Koganti et al, 2020 ). The sustained presence of myelin debris at the injury site of the spinal cord leads to neurological functional recovery failure because the accumulation of myelin debris containing inhibitor molecules resists axon regeneration ( Cunha et al, 2020 ; Liu Y. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the phagocytic capacity of macrophages could be a potential therapeutic strategy for SCI treatment. A few transcriptome analysis studies demonstrated that microglial cells could express high levels of certain specific genes, including Sall-1, Siglec-H, TMEM119, and P2RY12, which could be considered potential microglia-specific markers ( Doring et al, 2015 ; Guo et al, 2016 ; Kucharova and Stallcup, 2017 ; Koganti et al, 2020 ). However, there is still no widely accepted cell marker to distinguish between BMDMs and microglia in the CNS, which needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue was then dehydrated, and cleared in methyl salicylate before observing the whole brain ("brain wholemount") under the fluorescent microscope. An example of filled, uninjured M-axons in the cleared brain wholemounts can be seen in Figure 1 of Koganti et al (2020). Occasionally other axons were inadvertently filled with dye.…”
Section: Lucifer Yellow Fill Techniquementioning
confidence: 99%
“…This technique was used prior to Lucifer yellow injections of the proximal and distal segments of the M-cell (see Figure 9). A more detailed account of this technique can be found in Koganti et al (2020).…”
Section: Selective Axotomy Techniquementioning
confidence: 99%
See 1 more Smart Citation